2010
DOI: 10.1590/s1516-35982010001100011
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre características morfológicas e produtivas de clones de palma-forrageira

Abstract: RESUMO -Objetivou-se avaliar a relação entre as características morfológicas e produtivas de clones de palma-forrageira para identificação daqueles que contribuem diretamente na produção. Foram avaliados 50 clones de palma-forrageira estabelecidos no palmal há cinco anos e submetidos ao primeiro corte dois anos antes da avaliação. Foram avaliadas as características da planta e do cladódio, e os dados foram analisados pela estatística descritiva, correlação de Pearson e pela análise de trilha das variáveis-inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
2
26

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 9 publications
6
23
2
26
Order By: Relevance
“…The similarity between the data of plants in the soil with and without P may have occurred because 'Gigante' cactus has low capacity of response to phosphate fertilization, with positive performance only when the P content in the soil is lower than 10 mg dm -3 (Dubeux Júnior et al, 2010), a situation close to that in the present study, in which soil P content was 10.6 mg dm -3 . Dubeux Júnior et al (2010) observed no effect of P, K and their interaction on the number of cladodes.…”
Section: Resultssupporting
confidence: 81%
“…The similarity between the data of plants in the soil with and without P may have occurred because 'Gigante' cactus has low capacity of response to phosphate fertilization, with positive performance only when the P content in the soil is lower than 10 mg dm -3 (Dubeux Júnior et al, 2010), a situation close to that in the present study, in which soil P content was 10.6 mg dm -3 . Dubeux Júnior et al (2010) observed no effect of P, K and their interaction on the number of cladodes.…”
Section: Resultssupporting
confidence: 81%
“…A média dos parâmetros produtivos encontrados no presente estudo (Figura 1) está acima daquelas verificadas por outros autores (Flores-Hernández et al, 2004;Silva et al, 2010;Nascimento et al, 2011).…”
Section: Resultsunclassified
“…On the other hand, the growth of these cladodes is expected to result in reduction of the dimensions of lower cladodes. Silva et al (2010), in study conducted with 50 clones, observed that the basal and first-order cladodes showed the largest morphological dimensions since they support the plant; however, proportional reductions of these dimensions were observed with the appearance of cladodes of higher orders.…”
Section: Resultsmentioning
confidence: 92%
“…In turn, plant width has been cited as good variable to be adopted in the selection of more-productive clones (Silva et al, 2010;Pinheiro et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation